Identification of the passion fruit (Passiflora edulis Sims) MYB family in fruit development and abiotic stress, and functional analysis of PeMYB87 in abiotic stresses - Zhang, Yan-shu; Xu, Yi; Xing, Wen-ting; Wu, Bin; Huang, Dong-mei; Ma, Fu-ning; Zhan, Ru-lin; Sun, Pei-guang; Xu, Yong-yan; Song, Shun (Frontiers in Plant Science, 2023)
Environmental stresses are ubiquitous in agricultural cultivation, and they affect the healthy growth and development of edible tissues in passion fruit. The study of resistance mechanisms is important in understanding the adaptation and resistance of plants to environmental stresses. In this work, two differently resistant passion fruit varieties were selected, using the expression characteristics of the transcription factor MYB, to explore the resistance mechanism of the MYB gene under various environmental stresses. A total of 174 MYB family members were identified using high-quality passion fruit genomes: 98 2R-MYB, 5 3R-MYB, and 71 1R-MYB (MYB-relate). Their family information was systematically analyzed, including subcellular localization, physicochemical properties, phylogeny at the genomic level, promoter function, encoded proteins, and reciprocal regulation. In this study, bioinformatics and transcriptome sequencing were used to identify members of the PeMYB genes in passion fruit whole genome data, and biological techniques, such as qPCR, gene clone, and transient transformation of yeast, were used to determine the function of the passion fruit MYB genes in abiotic stress tolerance. Transcriptomic data were obtained for differential expression characteristics of two resistant and susceptible varieties, three expression patterns during pulp development, and four induced expression patterns under abiotic stress conditions. We further focused on the resistance mechanism of PeMYB87 in environmental stress, and we selected 10 representative PeMYB genes for quantitative expression verification. Most of the genes were differentially induced by four abiotic stresses, among which PeMYB87 responded significantly to high-temperature-induced expression and overexpression of the PeMYB87 gene in the yeast system. The transgenic PeMYB87 in yeast showed different degrees of stress resistance under exposure to cold, high temperatures, drought, and salt stresses. These findings lay the foundation for further analysis of the biological functions of PeMYBs involved in stress resistance in passion fruit